Genotype–phenotype correlation in 21 patients with Wolf–Hirschhorn syndrome using high resolution array comparative genome hybridisation (CGH). Issue 2 (14th September 2007) - Maas, N M C; Van Buggenhout, G; Hannes, F; Thienpont, B; Sanlaville, D; Kok, K; Midro, A; Andrieux, J; Anderlid, B-M; Schoumans, J; Hordijk, R; Devriendt, K; et al.
Abstract : Background: The Wolf-Hirschhorn syndrome (WHS) is usually caused by terminal deletions of the short arm of chromosome 4 and is phenotypically defined by growth and mental retardation, seizures, and specific craniofacial manifestations. Large variation is observed in phenotypic expression of these features. In order to compare the phenotype with the genotype, we localised the breakpoints of the 4pter aberrations using a chromosome 4 specific tiling BAC/PAC array. Methods: In total, DNA from 21 patients was analysed, of which 8 had a cytogenetic visible and 13 a submicroscopic deletion. Results and conclusion: In addition to classical terminal deletions sized between 1.9 and 30 Mb, we observed the smallest terminal deletion (1.4 Mb) ever reported in a patient with mild WHS stigmata. In addition, we identified and mapped interstitial deletions in four patients. This study positions the genes causing microcephaly, intrauterine and postnatal growth retardation between 0.3 and 1.4 Mb and further refines the regions causing congenital heart disease, cleft lip and/or palate, oligodontia, and hypospadias.